Study of Groundwater Salinity Distribution in Coastal Areas, Adimulyo Sub-district, Kebumen Regency, Central Java - Winarno; Agung Adiputra (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2022)
Groundwater salinization occurs in Adimulyo Sub-district, Kebumen Regency due to human activities. A very slow river flow, due to its small hydraulic gradient towards the estuary area. Reduced groundwater due to increased uptake by human activities causes intrusive river water which results in brackish groundwater. The data analysis carried out in the study was based on the primary data of the sample whose groundwater salinity was measured, showing the influence of the salt solution at a certain level which indicates a level of salinity with a negative chloride ion content. The salinity value belongs to the type of brackish water. Electrical Conductivity Groundwater shows the nature of conducting electricity from water. The highest groundwater salinity is in the area of Adimulyo Sub-district, Kebumen Regency, the middle part, which ranges from 4.45 "° - 10.15 "°. There are other factors besides the distance of the area from the coastline, namely brackish river water (estuary), and the large amount of groundwater withdrawal by residents which can increase the absorption of brackish river water (estuary) into groundwater. In the northern part of Adimulyo Sub-district, Kebumen Regency is an area that has the lowest groundwater salinity, which ranges from 0.12 "° - 2.50 "°. As for the area of Adimulyo Sub-district, Kebumen Regency, the South has medium groundwater salinity, which ranges from 0.80 "° - 2.87 "°.